KARAKTERISTIK PROFIL METAKOGNISI SISWA DALAM PENYELESAIAN MASALAH MATEMATIS TINGKAT TINGGI (HIGH ORDER THINKING) DITINJAU DARI DISPOSISI MATEMATIS SISWA - Anggoro, Bambang Sri (JURNAL e-DuMath, 2018)
AbstractStudying and tracking the metacognitive characteristics of students is necessary to be able to choose the strategy or learning method that will be used. This study aims to see how the characteristics of metacognitive profiles of students in the completion of high-order mathematical problems (high order thinking) in terms of mathematical disposition of students and to see the effect of learning that focuses on metacogntif on learning outcomes. Based on the result of the research, it is found that students with high disposition category are able to finish each stage of solving of high level mathematical problem, whereas in low category students still not complete complete problem stages. Stages passed by the students of the low disposition category is the stage of evaluation is to check back the results of answers. In the calculation results using statistical tests also obtained that students who applied learning that focuses on more have a higher learning outcome value when compared with ordinary learning.Â Keywords: Metacognitive, High Order Thinking, Disposition Mathematics